ANALISIS EFISIENSI BANK PEMBANGUNAN DAERAH DI INDONESIA; PENDEKATAN STOCHASTIC FRONTIER ANALYSIS - Yudaruddin, Rizki (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2017)
Stochastic Frontier Approach (SFA) is a technique of measuring the level of efficiency with a parametric approach. The purpose of this study examines the sharing factors affecting the efficiency of regional development banks in Indonesia. Using panel data sourced from Bank Indonesia and the Central Bureau of Statistics Year 2009-2015, the model analysis was used to measure the efficiency of banking using SFA. Data were analyzed by Panel Data Regression using E-Views program 8. The study found the bank's profitability as measured by ROA significant negative effect, while NIM significant positive effect. For variable risk of significant positive effect while the stability of banks has a negative influence and insignificant. The size of the bank and depositor funds not significant effect on the efficiency of the bank. GDP variables showed significant positive results. As for the inflation variable was found negative and not significant to efficiency